Integrating phylogenetic and ecological distances reveals new insights into parasite host specificity - Clark, N; Clegg, S (Wiley, 2017)
The range of hosts a pathogen infects (host specificity) is a key element of disease risk that may be influenced by both shared phylogenetic history and shared ecological attributes of prospective hosts. Phylospecificity indices quantify host specificity in terms of host relatedness, but can fail to capture ecological attributes that increase susceptibility. For instance, similarity in habitat niche may expose phylogenetically unrelated host species to similar pathogen assemblages. Using a recently proposed method that integrates multiple distances, we develop a new index to assess the relative contributions of host phylogenetic and functional distances to pathogen host specificity (functional-phylogenetic host specificity). We apply this index to a dataset of avian malaria parasite (Plasmodium and Haemoproteus spp.) infections from Melanesian birds to show that multi-host parasites generally use hosts that are closely related, not hosts with similar habitat niches. We also show that host community phylogenetic ß diversity (Pßd) predicts parasite Pßd, and that individual host species carry phylogenetically clustered Haemoproteus parasite assemblages. Our findings were robust to phylogenetic uncertainty, and suggest that phylogenetic ancestry of both hosts and parasites play important roles in driving avian malaria host specificity and community assembly. However, restricting host specificity analyses to either recent or historical timescales identified notable exceptions, including a ‘habitat specialist’ parasite that infects a diversity of unrelated host species with similar habitat niches. This work highlights that integrating ecological and phylogenetic distances provides a powerful approach to better understand drivers of pathogen host specificity and community assembly.